2021
DOI: 10.1210/clinem/dgab448
|View full text |Cite|
|
Sign up to set email alerts
|

The Use of Morning Urinary Gonadotropins and Sex Hormones in the Management of Early Puberty in Chinese Girls

Abstract: Context Although gonadotropin-releasing hormone stimulation test (GnRHST) is the gold standard in diagnosing central precocious puberty (CPP), it is invasive, expensive, and time-consuming, requiring multiple blood samples to measure gonadotropin levels. Objective We evaluated whether urinary hormones could be potential biomarkers for pre- or post- puberty, aiming to simplify the current diagnosis and prognosis procedure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Biomarker tests in fingertip blood and spot urine samples can be used to diagnose reproductive diseases and to monitor reproductive health. , These tests are noninvasive and cost-effective compared to traditional blood tests. We tested fingertip blood and urine samples separately using the proposed quadruplex immunoassay.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Biomarker tests in fingertip blood and spot urine samples can be used to diagnose reproductive diseases and to monitor reproductive health. , These tests are noninvasive and cost-effective compared to traditional blood tests. We tested fingertip blood and urine samples separately using the proposed quadruplex immunoassay.…”
Section: Resultsmentioning
confidence: 99%
“…The simultaneous measurement of FSH, LH, PRL, and AMH can provide a comprehensive hormonal profile that is useful in assessing the stage of pubertal development, identifying underlying disorders, and differentiating between central and peripheral causes. , Therefore, the simultaneous assessment of the four reproductive hormone protein levels is of great importance for the detection of reproductive health. Furthermore, the change of urinary FSH, LH, and PRL levels also indicates the problems of reproductive health and demonstrates the efficacy of fertility treatments. , Nevertheless, recent studies have failed to detect the presence of AMH in urine. , Therefore, it is essential to conduct a thorough exploration into urinary AMH levels with the assistance of a more sensitive detection technique for studying the relationship between AMH levels and the development of related diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison with morning or random micturition would be of high interest. Previous studies have agreed that there is no benefit in calculating the urinary gonadotropins/urinary creatinine ratio; this does not refine correlation of values with breast Tanner stages ( Zhan et al , 2021 ), and even impairs it ( Demir et al , 2021 ). Moreover, Singh et al (2015) showed in a large cohort of teenagers that an adjustment of steroid or urinary LH assays on hydration status (osmolality, specific gravity, urine creatinine) did not confer an improved relevance of the results.…”
Section: Discussionmentioning
confidence: 98%
“…The measurement of FSH and LH in urine samples was previously reported to be a useful biological tool to detect the pubertal increase of gonadotropin secretion ( Buckler and Clayton, 1970 ; Rifkind et al , 1970 ; Chipman et al , 1981 ). Several studies have reported interesting results regarding the usefulness of first-morning voided (FMV) or random non-timed urines to detect puberty onset with good sensitivity in girls ( McNeilly et al , 2012 ; Zung et al , 2014 ; Demir et al , 2016 , 2021 ; Lucaccioni et al , 2016 ; Kolby et al , 2017 ; Shim et al , 2019 ; Yüce et al , 2020 ; Lee et al , 2021 ; Zhan et al , 2021 ). The collection of 24-h urine samples provides the complete nychthemeral activity of the HPG axis and the data correlates well with that from morning urine samples ( Maesaka et al , 1990 ).…”
Section: Introductionmentioning
confidence: 99%